An Interview Report on Users’ Perception about the Usability Performance of a Mobile E-Government Application - Hussain, Azham; Mkpojiogu, Emmanuel O.C.; Ishak, Norzila; Mokhtar, Nurhidayah; Che Ani, Zhamri (International Journal of Interactive Mobile Technologies (iJIM), 2019)
Mobile governance enables citizens to comfortably do business with government anywhere, any time. This provides an enriching experience to users as they use these platforms in their convenience and with comfort. MyEG Services Berhad ("MyEG") is a concessionaire for Malaysian Electronic-Government ("E-Government") MSC Flagship Application. MyEG manages the electronic channel that offers services from various Government agencies to the Malaysian citizens and businesses. The MyEG developed a mobile application that can be used to check summons, pay summons, renew road-tax and renew auto insurance. In this study, a usability assessment was done using interview approach to examine the experience of users (with regard to usability) of the mobile application. The interview was carried out after participants engaged and interacted with the application in some task’s scenarios. The assessment was done at Jabatan Teknologi Maklumat and Komunikasi, Politeknik Seberang Perai, with 15 volunteers who consisted of lecturers and students. The findings showed that overall the application was perceived usable and also enriched the experience of participants. However, there were some improvements that should be implemented in the area of findability to further improve on users’ satisfaction and felt experience.Mobile governance enables citizens to comfortably do business with government anywhere, any time. This provides an enriching experience to users as they use these platforms in their convenience and with comfort. MyEG Services Berhad ("MyEG") is a concessionaire for Malaysian Electronic-Government ("E-Government") MSC Flagship Application. MyEG manages the electronic channel that offers services from various Government agencies to the Malaysian citizens and businesses. The MyEG developed a mobile application that can be used to check summons, pay summons, renew road-tax and renew auto insurance. In this study, a usability assessment was done using interview approach to examine the experience of users (with regard to usability) of the mobile application. The interview was carried out after participants engaged and interacted with the application in some task’s scenarios. The assessment was done at Jabatan Teknologi Maklumat and Komunikasi, Politeknik Seberang Perai, with 15 volunteers who consisted of lecturers and students. The findings showed that overall the application was perceived usable and also enriched the experience of participants. However, there were some improvements that should be implemented in the area of findability to further improve on users’ satisfaction and felt experience.